Interindustry Mobility and the Cyclical Upgrading of Labor - McLaughlin, Kenneth J.; Bils, Mark (Journal of Labor Economics, 2001)
We investigate whether a market‐clearing model is consistent with industry employment and wage patterns related to the cyclical upgrading of labor. We demonstrate that Roy's (1951) market‐clearing model of self‐selection would account for cyclical upgrading if industries were characterized by positive selection. Wage comparisons of industry movers and stayers in panel data do reveal widespread positive selection. Also consistent with the Roy model, composition‐corrected industry wages are more cyclical in high‐wage cyclical industries. The Roy model does fail to explain predictable patterns in the wage changes of industry movers, so we consider several market‐clearing and queuing extensions.